A Study to Measure the Efficacy of a Manualised Oral Narrative Intervention Programme for School-age Children with Narrative Delay - Glisson, Laura (Curtin University, 2017)
This study evaluated the efficacy of a manualised oral narrative intervention programme designed for children with oral narrative delay. Using a single-subject multiple baselines design, the intervention was delivered by a speech pathologist to 11 children aged 5;0-5;11 years, in small groups, three times a week for six weeks. The findings supported the effectiveness of explicit teaching of macrostructure and repeated retellings of stories, on improving macrostructure and microstructure elements of generated narratives.